Immunoglobulins Levels and Complements in Patients with Brain Tumour (Meningioma and Glioma) - turki, salwa (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): The present study aims at studying the relationship between immunoglobulin IgG, IgA, IgM , as well as to C-3 and C-4 in brain tumours patients immunity (meningioms and gliomas). Methodology: Forty sera of brain tumour patients were included 20 glioma and 20 meningioma was tested to determine the levels of IgM, IgG IgA, C-3 and C-4 by using single radial immune-diffusion technique and compared with 20 apparently healthy blood donors. Results: The study revealed a significant decreasing in IgG levels in glioma as compare to meningioma and control. The concentration of two other serum immunoglobulins and complement in both meningioma and glioma show no significant differences with those in control group. Recommendations: The study recommends using serum and tissues in molecular level in other type of brain tumour with different grades.